The Relationship between Strategic Management Practices and Financial Performance: The Moderating Role of Business Intelligence - Barakat, Shaima A Kh; Hamed, Adel Abdullatif Ahmad; Dandan, Sameer Mohammed Majed; Farah, Amira AH (South Asian Journal of Social Sciences and Humanities, 2024)
Financial performance is a subjective assessment of a firm’s ability to use assets from its core business operations to create income. The phrase is utilized as a comprehensive indicator of a company’s financial well-being throughout a certain duration. Strategic management practices play a crucial role in determining the financial performance of organizations. This paper aims to critically analyzed the impact of strategic management practices on financial performance by examining various scholarly articles and studies in the field. Moreover, the influence of business intelligence as a moderator on the relationship between strategic management practices and the financial performance of SMEs in the northern region of Malaysia was also investigated. This study amalgamated the resource-based view (RBV) to elucidate the impact of the factors on effective strategy execution. Questionnaires were administered to 378 SMEs in the northern region of Malaysia. The above sample was utilized in the analysis employing the Structural Equation Modelling (SEM) - Partial Least Squares (PLS) approach. The study’s results indicated a substantial impact of strategic management practices on financial performance. The research indicated that the moderating influence of business intelligence on strategic management practices and financial performance was significant. This study emphasized the research ramifications, recommendations for further investigations, and its limits.